Evaluación de dos abonos orgánicos y químicos (gallinaza, estiércol bovino, 10-30-10 y 15-15-15) a tres niveles en campanas de Irlanda (Molucella,leavis) de corte en el cantón-Saquisili - Remache Aimacaña, Alicia Margoth (2013)
In the present investigation raised the topic called "Evaluation of two organic and chemical fertilizers (manure, cow manure, 10-30-10 and 15-15-15) at three levels in the cultivation of Bells of Ireland (Molucella leavis), "cut, the study was conducted at Loma Cruz neighborhood located in the canton Saquisili The overall objective was to evaluate two organic and chemical fertilizers (manure, cow manure, 10-30-10 and 15-15-15) at three levels in the cultivation of Bells of Ireland (Molucella leavis) "cut in the canton Saquisili. The specific objectives were to determine the best organic manure and chemical farming Bells of Ireland (Molucella leavis). Determine what level influences growing (Molucella leavis) Perform economic analysis of best treatment.